El arbol generoso - Silverstein, Shel (Caracas : Litexsa Venozolana, 1988)
Un muchacho crece a la juventud a la ancianidad experimentando el amor y la generosidad de un arbol que le da sin esperar que su amor sea correspondido.
A young boy grows to manhood and old age experiencing the love and generosity of a tree that gives to him without thought of return.
Original title: The giving tree
Accelerated Reader
Accelerated Reader AR
Text in Spanish.
Keywords: Trees -- Juvenile fiction; Arboles -- Novela juvenil